Conic-Based 3D Rockfall Modeling with QGIS-Qproto Software: A Case Study of Mazı Village, Nevşehir (Ürgüp) - Mustafa Utlu; Mehmet Fatih Akgümüş (Doğal Afetler ve Çevre Dergisi)
This study focuses on the high-resolution 3D cone-based rockfall modeling using Qproto, a QGIS plugin, based on UAV-DSM data in an area near Mazı Village, located north of Derinkuyu and Ürgüp districts in Nevşehir province, where rockfall events occur intensively. The volcanic ignimbrites corresponding to the source zones in the study area have steep and vertical slope profiles, particularly resembling cornices. Therefore, 16 rock blocks with a potential for rockfall were identified within the rock mass structure characterized by cooling cracks (vertical discontinuities) commonly observed in ignimbrites where discontinuities near the vertical occur. Rockfall modeling was performed for these identified blocks. According to the modeling results, rockfalls with a maximum kinetic energy of 142 kJ and a displacement velocity of 16.8 m/s were determined. Based on these results, the maximum values of the rockfall model within the study area were generally reached in areas with high slope values, and it was observed that the energies and velocities of rock blocks attenuated at points with decreased slope, indicating the influence of the existing gravitational condition. Rockfall susceptibility degrees were categorized into five classes, and it was observed that the trajectories of fallen blocks, resulting from rockfalls, corresponded mainly to the moderate-high and high susceptibility classes, where they were scattered and dispersed.